Characterization of a synthetic zinc‐chelating peptide from sea cucumber (Stichopus japonicus) and its gastrointestinal digestion and absorption in vitro. (19th February 2022) - Wang, Zixu; Sun, Jiatong; Ma, Xiaoyu; Liu, Xiaoyang; Yin, Fawen; Li, Deyang; Nakamura, Yoshimasa; Yu, Chenxu; Zhou, Dayong
Abstract: BACKGROUND: Zinc absorption in intestinal system could be strongly affected by the gastrointestinal digestion and absorption of zinc‐chelating peptides serving as zinc carriers. In this study, a novel zinc‐chelating sea cucumber synthetic peptide (SCSP) was synthesized to estimate its gastrointestinal digestion and promotive effect of zinc absorption in vitro . RESULTS: Analysis of isothermal titration calorimetry suggested that the binding of SCSP and zinc ( N ≈ 1) was exothermic, with relatively weak binding affinity ( K = 1.0 × 10 −3 mol L −1 ). The formation of SCSP–Zn complexes brought morphological changes to the peptides confirmed by scanning electron microscopy (SEM), which also indicated 6.88% of the existence of zinc element. In addition, the SCSP–Zn complexes remained stable under simulated human gastrointestinal digestion. In an in vitro study, the SCSP–Zn complex could successfully transport through the intestinal membrane in the model of everted rat gut sacs (nearly 7.5 μM cm −2 ) as well as Caco‐2 cells where the zinc transport reached 0.0014 mg mL −1 carried by SCSP. Fluorescence staining experiments revealed free zinc accumulation inside the tissues and cells treated with the SCSP–Zn complex. CONCLUSIONS: The chelation SCSP–Zn had the promotion ability of zinc absorption in vitro and ex vivo experiments, which suggested a theoretical basis for the design and production of effective zinc chelating peptides as zinc carriers to improve zinc bioavailability. © 2022 Society of Chemical Industry.